Représentations d’opéra et représentation de l’opéra dans deux romans de l’époque victorienne et édouardienne - Pierre Degott (Cahiers Victoriens et Edouardiens)
This paper aims at studying the function of opera performances, as staged in two novels from the Victorian and Edwardian period: Henry James’s The American and E. M. Forster’s Where Angels Fear to Tread. The paper mainly focuses on the intertextual value of the musical pieces included in the two novels, but also on the nature of the performing act per se. In James’s work, opera is used to illuminate some of the elements of the plot, although it can also contribute to the ambiguities of the novel. Opera also plays a major structural role in both works, quickening and catalysing the action. However, opera in The American hardly ever goes beyond the purely mimetic function of the work of art, whereas its presence literally influences the lives and actions of two participants in Forster’s novel. In the latter work, opera appears as a « transforming agent, » able to transfigure all those who are sensitive to the power of art. In Where Angels Fear to Tread, the aptly named « performing arts » do actually perform.